Aplikasi Media Pembelajaran Praktik Sholat Idul Fitri Menggunakan Augmented Reality Berbasis Android - Adlani, Farid; Ikhwan, Ali; Amanda Putri, Raissa (Bulletin of Computer Science Research, 2023)
The problem of this research is the lack of interactive and interesting resources to help individuals understand and perform Eid prayers correctly, as well as the lack of learning time given to students related to learning prayer practices. To overcome this problem, this research develops a learning media application for Eid prayer practices that uses augmented reality with the Android-based Marker Based Tracking Method. The development model used is the Research and Development (R&D) development model. The results of this study indicate that based on the benefit aspect questionnaire data, the calculation of the percentage score of the application benefit aspect shows a result of 83.75%. Meanwhile, the visual communication aspect received a percentage score of 82.19%. Both aspects fall into the good category, indicating that this application is feasible to use as learning media.